Kinetics and Mechanism of Hydrolysis of Mono-2-Chloro 4-Nitrophenyl Phosphate - Shinde, C.P.; Patil, R. (Asian Journal of Chemistry, 2010)
Kinetic study of mono-2-chloro 4-nitrophenyl phosphate has been carried out in acid medium at 98 ± 5ºC. Colorimetric method has been employed for the estimation of inorganic phosphate, the ultimate product of hydrolysis. Pseudo-first order rate coefficients have been calculated. In the acid region protonate acid species and neutral species have been found to be reactive. The calculated rate coefficients are in good agreement with the experimentally observed rates. The effect of pH, salt, temperature, solvent, solvent isotope and substrate concentration have been studied on the rate of hydrolysis.